Tucumán 1965-1969: movimiento azucarero y radicalización política - Ana Julia Ramírez (Nuevo mundo - Mundos Nuevos, 2008)
This article studies the cycle of protests that took place in the Argentinean province of Tucumán between 1965-1969.This is done as a mean to inquiry into an early experience of working-class radicalization and of fast transformation, at the heat-peak of structural-economic change and also of political repression carried out by the dictatorship of the “Revolución Argentina” since 1966. The study of this local experience will allow us to problematize linear narratives and established chronologies regarding the wider process of political radicalization developed in Argentina during the sixties and seventies.